The State of Lung Cancer Research: A Global Analysis. Issue 7 (July 2016) - Aggarwal, Ajay; Lewison, Grant; Idir, Saliha; Peters, Matthew; Aldige, Carolyn; Boerckel, Win; Boyle, Peter; Trimble, Edward L.; Roe, Philip; Sethi, Tariq; Fox, Jesme; Sullivan, Richard
ABSTRACT : Introduction: : Lung cancer is the leading cause of years of life lost because of cancer and is associated with the highest economic burden relative to other tumor types. Research remains at the cornerstone of achieving improved outcomes of lung cancer. We present the results of a comprehensive analysis of global lung cancer research between 2004 and 2013 (10 years). Methods: : The study used bibliometrics to undertake a quantitative analysis of research output in the 24 leading countries in cancer research internationally on the basis of articles and reviews in the Web of Science (WoS) database. Results: : A total of 32, 161 lung cancer research articles from 2085 different journals were analyzed. Lung cancer research represented only 5.6% of overall cancer research in 2013, a 1.2% increase since 2004. The commitment to lung cancer research has fallen in most countries apart from China and shows no correlation with lung cancer burden. A review of key research types demonstrated that diagnostics, screening, and quality of life research represent 4.3%, 1.8%, and 0.3% of total lung cancer research, respectively. The leading research types were genetics (20%), systemic therapies (17%), and prognostic biomarkers (16%). Research output is increasingly basic science, with a decrease in clinical translational research output during this period. Conclusions: : Our findings have established that relative to the huge health, social, and economic burden associated with lung cancer, the level of world research output lags significantly behind that of research on other malignancies. Commitment to diagnostics, screening, and quality of life research is much lower than to basic science and medical research. The study findings are expected to provide the requisite knowledge to guide future cancer research programs in lung cancer.